Religious and church-administration situation in the Chrudim region in the 18th century from the perspective of confession reports - Nekvapil, Ladislav (Theatrum historiae, 2011)
This study deals with the development of the religious and church-administration situation in what was then the Chrudim region from the Battle of White Mountain until the early Tolerance period; the work mainly focuses on the 18th century. The main sources used for this topic included confession lists and reports from the Prague Archdiocese from 1671–1781 in combination with Catalogus cleri (lists of priests) from 1741 and 1771. This article is also based on the population census by their faith from 1651 in order to outline the religious situation in the 17th century. First, the article briefly depicts the religious situation in the Chrudim region from the perspective of long-term development, pointing out the main factors of the preservation of folk religion mainly in rural areas in the period after the Battle of White Mountain. Specific examples from noble and civic circles illustrate the basic features of the recatholisation witnessed by the Chrudim region in the period after White Mountain. Using the above- mentioned census by faith for the Chrudim region, it is possible to outline the structure of confessions of the inhabitants registered at farmsteads, manors and in towns in the mid-17th century, while taking geographic and landscape factors into account. The core of the study is based on an analysis of confession reports from 1737–1781 processed in five-year intervals. This type of source is first briefly introduced as to its structure and information value since researchers have not used it in a complex way so far. Subsequently, we observe the situation in church administration in the Chrudim region in the 18th century, using the Catalogus cleri (1741, 1771); we focus on the metamorphoses of the vicarage and presbytery network, where the important factors of recatholisation in- cluded mainly the upswing of the institute of chaplain, which was enabled by an enormous growth of the auxiliary clergy. This resulted not only in the change of most subsidiary churches into chapels which were continuously occupied by chaplains, but also improve- ment of the quality and growth of the density of the catholic network, which was one of the key factors in the Roman Catholics' fight against non-Catholics. Similarly, the 18th century saw large vicarage districts divided into several smaller ones, the administration of which was far more efficient. The following part of this work observes the development of the numbers of Catho- lics and non-Catholics in the Chrudim region in the 18th century, while it also respects the qualitative distinction of the levels of non-Catholic manifestations. At the same time, it also investigates, from a temporal perspective, the causes of fluctuations of the numbers of non- Catholics, their activation (or activation of Evangelic emigration) as well as other factors influencing their survival and resistance in the folk environment in Bohemia. This also leads to the question of coexistence of Catholics and non-Catholics in rural settings. As a conclusion, the work evaluates the success of recatholisation efforts given the high numbers of persons who became members of the newly formed Evangelic churches in the period following the issuance of the Edict of Tolerance. At the same time, it compares the areas where non-Catholics prevailed in the mid-17th century with areas where most people claimed membership in non-Catholic confessions after the Edict of Tolerance; the work confirms that these areas significantly overlap.